2008
DOI: 10.1074/jbc.m804019200
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Escherichia coli Glutaredoxin-3 Substrate Specificity Using Ligand-induced Stability

Abstract: Traditionally, quantification of protein-ligand affinity is performed using kinetic or equilibrium measurements. However, if the binding reaction proceeds via a stable covalent complex, these approaches are often limited. By exploiting the fact that the conformational stabilization of a protein is altered upon ligand binding due to specific interactions, and using an array of selectively chosen ligand analogs, one can quantify the contribution individual interactions have on specificity. We have used ligand-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
(11 reference statements)
3
14
0
Order By: Relevance
“…Interestingly, in E. coli Grx2, which has the highest activity of the three bacterial dithiol Grxs toward 2-ME-SSG, the Lys is replaced by a Tyr. This supports previous reports that the characteristic ␥-glutamate moiety is more important for GSH recognition than the glycine part (43,44). In T. brucei Grx1 and Grx2, these substitutions probably support the interaction with T(SH) 2 (see below), in which the glycine carboxylate does not carry a negative charge but is engaged in an amide bond with the spermidine bridge.…”
Section: African Trypanosomes Possess Two Only Distantly Relatedsupporting
confidence: 90%
“…Interestingly, in E. coli Grx2, which has the highest activity of the three bacterial dithiol Grxs toward 2-ME-SSG, the Lys is replaced by a Tyr. This supports previous reports that the characteristic ␥-glutamate moiety is more important for GSH recognition than the glycine part (43,44). In T. brucei Grx1 and Grx2, these substitutions probably support the interaction with T(SH) 2 (see below), in which the glycine carboxylate does not carry a negative charge but is engaged in an amide bond with the spermidine bridge.…”
Section: African Trypanosomes Possess Two Only Distantly Relatedsupporting
confidence: 90%
“…However, it should be stressed that in E. coli Grx2, which has the highest HED reductase activity of the three bacterial dithiol Grxs (E. coli 2-C-Grx 1 to 3), the Lys is replaced by a Tyr. This supports previous reports that the characteristic c-Glu-Cys moiety is more important for GSH recognition than the glycine carboxylate (23,81). As will be outlined in this review, the trypanosomal 2-C-Grxs are involved in reactions with both GSH and/or T(SH) 2 .…”
Section: Trypanosomatids Possess Two Distantly Related Dithiol Glutarsupporting
confidence: 90%
“…The carboxylate of the glycyl moiety of the glutathionyl adduct is stabilized by H-bond donors or a positively charged lysine or both in most Grx-SSGs; however, a recent study of hGrx1 in which the interacting Lys was mutated to Leu or Gln resulted in retention of glutathionyl substrate specificity (58), suggesting that this specific ionic interaction is not required for reaction of Grx with the glutathionyl sulfur of the GS-containing mixed disulfide substrate. Moreover, analysis of the stability of mixed disulfides between E. coli Grx3 and various GSH analogues (28) suggested that the interaction between Grx and the glycyl group of the GS moiety contributes little to stabilization of the glutathionyl moiety in the Grx-SSG mixed disulfide intermediate.…”
Section: Reports Of Complex Formation Between Glutaredoxins and Glutamentioning
confidence: 99%